Is age more than a number? Accounting for adult development and aging in the study of psychoneuroimmunology, stress, and health - Stephanie J. Wilson (Comprehensive Psychoneuroendocrinology)
Traditional stress-and-health models link stressors to their health consequences through a well-characterized cascade. Most of the research assumes that the stress-health sequence unfolds in the same way across adulthood, whether a person is 25 years old or 80. Taking a “developmental” or “lifespan” approach has been synonymous with studying the lasting health impacts of early life experiences. However, theories and evidence from adult development and geroscience suggest that stress-health dynamics evolve in important ways over the adult lifespan—from the stressors that we encounter, to the emotion regulation strategies that we use to confront challenges, to the psychosocial resources at our disposal, to the cellular milieu, and thus to the magnitude of stressors' biological and functional consequences. This critical review synthesizes theoretical perspectives and selected empirical literature on the social-emotional and biological dimensions of aging to promote an Integrative Model of Aging, Stress, and Health. Through this integration, the model illustrates how an interdisciplinary, developmental perspective can enrich our understanding of stress's consequences for health across adulthood. It also seeks to guide a new generation of research questions that confront aging with a multidimensional approach. The piece concludes with personal reflections on the foundational legacy of the author's mentor, Dr. Janice Kiecolt-Glaser.